Eksternalizm illokucyjny a uwyraźnienie mocy illokucyjnej - Blanco Salgueiro, Antonio (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2006)
I call illocutionary externalism (IE) the approach to the study of illocutionary force that I favor. IE is inspired by Austin's seminal ideas on performatives and speech acts. According to IE, in the analysis of a paradigmatic illocutionary force we must essentially mention some aspects of the social and natural environment that cannot be reduced to the (de dicto) speakers' mental states, no matter how these are individuated. A difficult problem for IE derives from the possibility of making explicit the force of an utterance. This fact invites us to focus our attention on the utterer (the person who makes the force explicit) and his mental states (illocutionary intentions), and to support a mentalist approach in the study of forces. In this article I shall argue for the compatibility of IE with the phenomenon of the explicitability of illocutionary force.